Performance Audit on Implementation of Right to Education Act in Andhra Pradesh (2010-2017) - CAG of India (CAG of India)
The Right of Children to Free and Compulsory Education (RTE) Act, 2009 became operational with effect from 01 April 2010 to make elementary education a right of all children. The RTE Act provides right to free and compulsory education to all children in the age group of 6-14 years in a neighbourhood school from class 1 to class 8. Government of Andhra Pradesh notified the AP Right of Children to Free and Compulsory Education Rules (RTE Rules), 2010. Performance Audit of implementation of the RTE Act in the State was conducted covering the period from inception (2010-11) to 2016-17. An overview of findings of this Performance Audit is given below: Conduct of Survey RTE Rules, 2010 stipulated that Local authority should maintain a record of all children through a household survey from their birth till they attain the age of 14 years and the data should be updated each year. Scrutiny of records in the test-checked schools revealed that no household survey was conducted during 2010-17 to identify all the children in the age group of 6-14 years. (Paragraph 2.2.4.1) School mapping and neighbourhood schools RTE Rules provided for Mapping of schools to identify and establish Primary and Upper Primary schools within the neighbourhood (i.e., one and three km respectively from the habitation). Government had not conducted mapping of schools. (Paragraph 2.2.4.2) Targets for Enrolment and Trends of enrolment Government organised programmes like Badi Bata, Badi Pilustondi, Mana Vuru-Mana Badi to enroll students in Government Schools. However, the Gross Enrolment Ratio in respect of Primary classes decreased from 91 per cent in 2010-11 to 83 per cent in 2016-17. (Paragraphs 2.2.4.4 and 2.2.4.5) Dropout rate of children Child tracking system to monitor retention and academic progress of children, which the State Government had committed in 2010-11, was still not in place. (Paragraph 2.2.4.8) Pupil-Teacher Ratio There were no teachers in 1,014 Primary schools and 37 Upper Primary schools during 2016-17. Services of teachers from neighbouring schools/ Vidya Volunteers were being utilised in these schools. Audit observed in sampled schools that shortage of teachers was mainly in Mathematics, Science and Social Studies subjects which affected the performance of the children. (Paragraph 2.2.4.11) Supply of Uniforms Uniforms were to be supplied to children during June-August every academic year. Audit observed that uniforms were not supplied to 37 per cent of children in the test-checked schools. Audit observed in test-checked districts that during 2010-17, school uniforms were supplied during the months of December-April. (Paragraph 2.2.4.17) Appointment of Chartered Accountants A Selection committee was to select Chartered Accountant (CA) firm and the Executive Council of Sarva Shiksha Abhiyan (SSA) was to approve it. However, the Principal Secretary, School Education approved the appointment of Chartered Accountants without committee’s involvement from 2011-12. (Paragraph 2.2.5.7) State Advisory Council RTE Rules, 2010 envisaged constitution of a State Advisory Council chaired by the Minister for School Education to advise the State Government on implementation of the provisions of the Act in an effective manner. The Council was to meet once in every three months. Government constituted the Council belatedly in 2014, after four years of implementation of the Rules/Act. However, the Council had not conducted any meeting as of July 2017 due to pre-occupation of Council members. (Paragraph 2.2.6.1) Conclusion Comprehensive household survey of children in the age group of 6-14 years was not conducted. Government had not designed Geographical Information System (GIS) mapping to identify the availability of schools in the neighbourhood of habitations as stipulated. There was shortage of teachers at both Primary and Upper Primary levels. Infrastructure deficiencies continued. Department had not taken adequate steps to improve the learning levels and performance of students. Government was yet to achieve the objective of the ‘Right of Children to free and compulsory education’ Act.
For the Period 2010-2017